MEASURING AND ANALYZING THE IMPACT OF PUBLIC DEBT ON FOREIGN EXCHANGE RESERVES IN IRAQ FOR THE PERIOD (2003- 2020) - Khalil Ismail Aziz (Scholars Digest Publishing, 2024)
The investigation aims to gauge and explore the effects of public debt, both internal and external, on foreign exchange reserves in Iraq, which suffers from the problem of growing the volume of public debt and the consequent benefits of this debt that shackle the economy with more restrictions. The descriptive approach was used in the analysis of the theoretical framework supported by the quantitative inductive approach to measure this effect, and the time series of the study variables were stabilized when taking the first difference and the explanatory power of the model showed relative quality R-squared 92)While the results of polytheistic integration were the lack of a balanced relationship, and the reason for this is the government's dependence on financing public debt on external loans and stimulus policies, which greatly reduce the impact of public debt on foreign reserves.